SANDALWOOD AS A COMPONENT OF AGROFORESTRY: EXPLORATION OF PARASITISM AND COMPETITION WITH THE WANULCAS MODEL - Meine van Noordwijk; Albert Husein Wawo; Betha Lusiana; Jim Roshetko (BERITA BIOLOGI, 2001)
Sandalwood is an important component of agroforestry systems in the drier Eastern parts of Indonesia, although its value to farmers is still limited by existing policies and regulation of marketing. As a relatively slow growing root parasite, sandalwood will interact with other components in a complex pattern of competition and host-parasite relationships, depending on root distribution and rooting depth of potential hosts. We describe a number of modifications to the generic tree-soil-crop simulation model WaNuLCAS, that allow exploration of the transition between parasitism and competition. The key variable in this transition is the effectiveness of formation of the parasitic link for all situations where roots of the host and parasite occur in the same volume of soil. At low values of this effectiveness competition dominates, at higher values sandalwood will weaken the host, until it effectively kills it, leading to an optimum response of sandalwood to the effectiveness parameter. Unresolved questions in the formulation of the model are the lifespan of parasitized roots and the question whether or not sandalwood will allocate energy resources for maintenance respiration of host roots after the formation of haustoria. The'desk study' reported here was intended to focus subsequent field studies on these unresolved issues.